مسيرة الحضارةِ الإسلاميةِ التركيةِ في الأناضولِ بين الماضي والحاضر - YÜCER, Hür Mahmut (Journal of History Culture and Art Research, 2015)
Abstract This study endeavours to ascertain the bibliographical resources which the Anatolian Turks, an important component of Islamic history and civilization, have been nourished. Meanwhile it holds the style of civilization which they have constructed according to the course of these sources. Turks, after embracing Islam had used Persian and then Arabic as language of science. However most of the people who knew Turkish only, had formed their religious feelings through easy and brief texts which are easy to read and understand. In the Seljukids’ era the books such as Hamzanamah, Hz. Ali’nin Cenkleri (The Battles of the Caliph Ali) and Battalnamah had been publicly read while in the Ottomans’ era the people had read the books such as Mızraklı İlmihal (a book explaning principles of Islam), Ahmadiyah, Muhammadiyah. Great masses of people had composed intellectual and moral values by means of these books. This article strives to analyse how Anatolian people who repeatedly read the said texts over centuries through secondary institutions of culture which built itself. In the study descriptive analyze method is adopted.